Periodically patterned micro-cone textures as high-efficiency light harvesting structure for broadband absorption enhancement in thin film silicon solar cells. (1st January 2018) - Chen, Peizhuan; Niu, Pingjuan; Yu, Liyuan; Zhang, Jianjun; Fan, Qihua; Ning, Pingfan; Hou, Guofu
Graphical abstract: Highlights: A light harvesting structure based on Micro-Cone Patterned Substrate (MCPS) is proposed. The periodic micro-cone textured profiles are well preserved after film deposition. The influence of aspect ratio on MCPS-based solar-cell performances was examined. Full-spectral absorption enhancement was obtained for the MCPS-based solar cell. A 10.1% efficiency was achieved for the MCPS-based a-SiGe:H solar cell. Abstract: To further increase the efficiency of thin film solar cells, it is essential to enhance the absorption over the full spectral wavelength range in which solar cells generate electricity. Here, we present a broadband absorption enhancement method for n-i-p thin film silicon solar cells using Micro-Cone Patterned Substrates (MCPSs). The periodically patterned micro-cone textured profiles are well preserved after the deposition of each thin film layers, thus to fulfill with two critical criteria in solar energy harvesting by enhanced light in-coupling and light trapping. The influence of the aspect ratio (height/period) of the MCPSs on the optical and electrical performance of the hydrogenated amorphous silicon germanium (a-SiGe:H) solar cells is discussed via experiment. We demonstrate that MCPSs based solar cells allow us to achieve an electrical performance (open-circuit voltage and fill factor) comparable to what we obtain on flat and randomly nanotextured reference samples. Thanks to the full-spectral light harvesting enhancement, initial efficiency of 10.1% is obtained for the solar cell based on MCPS with aspect ratio of 0.5, which outperforms the planar (efficiency of 7.5%) and randomly nanotextured (efficiency of 8.7%) counter part by 34.7% and 16.1%, respectively. The micro-cone light harvesting structure can also be duplicated for other thin film photovoltaic devices and provides a new approach for creating high-efficiency thin-film solar cells.